Passenger satisfaction with public transport services in Lisbon Metropolitan Area - Lemos, Luís António da Silva (2022)
Public transport is a key-element on citizen mobility, in urban settings, in a more sustainable way, both socioeconomic and environmentally facing an urban reality that reveals problems of mobility traffic congestion and high pollution. Public transport operators are continually looking for ways to keep current passengers and attract new public transport users. In order to retain passengers and attract new ones, it is essential that entities involved in public transport identify and understand which aspects of public transport most influence the satisfaction and loyalty of its users. It is important to understand the perceptions, attitudes and behavior of passengers, as they are decisive in their satisfaction and intention to continue using these services, that is, their loyalty. This study aims to analyze the perceptions of users of public transport in metropolitan area of Lisbon, about different attributes of the modes they most commonly use and thus understand which of these have the greatest impact on passenger satisfaction. To this end, responses were obtained from citizens who use public transport in the metropolitan area of Lisbon at least once a week, where they expressed their opinions about various attributes of the modes of public transport, they use such as safety, reliability, comfort, among others. In general, the bus has proved to be the transport mode that gathers the worst opinions among public transport users. The attributes of safety, reliability and comfort were the ones that showed the most discrepancies among those questioned.